2012
DOI: 10.3109/0142159x.2012.687490
|View full text |Cite
|
Sign up to set email alerts
|

Virtually present: The perceived impact of remote facilitation on small group learning

Abstract: Background: The engagement of facilitators located remotely for small group learning has received little research attention. However, this approach could increase the pool of experts for small group learning, thus addressing challenges to sustainability faced by in-person models of small group facilitation. Aim: The objective of this study was to describe the experiences and perceptions of students regarding the use of remote facilitation for small group learning in a health education setting. Methods: This qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…A NL study around rural communities found that technology allowed for ways for community to come together, individuals to take on leadership/supervisory roles, and there was excitement for using it to take courses and learn new skills (Clover, 2007). Such online, facilitated workshops should include careful planning around technology itself as well as its implementation (e.g., set-up of space, carefully chosen facilitator, group dynamics; Davies, Yeung, Mori, & Nixon, 2012). Space for communication (e.g., a collaborative live chat feature) acting, reflecting, thinking and feeling-and to take charge of learning (Kolb 2000) should be included-in a live, didactic manner.…”
Section: Online Trainingmentioning
confidence: 99%
“…A NL study around rural communities found that technology allowed for ways for community to come together, individuals to take on leadership/supervisory roles, and there was excitement for using it to take courses and learn new skills (Clover, 2007). Such online, facilitated workshops should include careful planning around technology itself as well as its implementation (e.g., set-up of space, carefully chosen facilitator, group dynamics; Davies, Yeung, Mori, & Nixon, 2012). Space for communication (e.g., a collaborative live chat feature) acting, reflecting, thinking and feeling-and to take charge of learning (Kolb 2000) should be included-in a live, didactic manner.…”
Section: Online Trainingmentioning
confidence: 99%
“…Asynchronous, or delayed, telehealth technologies disseminate evidence-based interventions through the self-administration of intervention tools or by providing training materials through recordings of clinical protocols or documents through patient portals and websites (Epstein et al, 2008). Synchronous and asynchronous telehealth technologies show potential for distance training of community-based clinicians in evidence-based treatments of complex disorders (Archambault, Mansfield, Evans, & Keitner, 2014; Davies, Yeung, Mori, & Nixon, 2012; Siminerio, Ruppert, Huber, & Toledo, 2014; Socolovsky et al, 2013). …”
mentioning
confidence: 99%
“…The importance of facilitators for CAP workshops has been reported previously, 4 but there has been a lack of consensus on whether facilitator expertise or facilitation skills were the more valuable attribute for student learning with remotely located facilitators. 12 By being physically present, the positive bene ts provided through the facilitator's personality attributes and skills could be maximized.…”
Section: Discussionmentioning
confidence: 99%